2022
DOI: 10.1038/s41523-022-00444-8
|View full text |Cite
|
Sign up to set email alerts
|

Ductal keratin 15+ luminal progenitors in normal breast exhibit a basal-like breast cancer transcriptomic signature

Abstract: Normal breast luminal epithelial progenitors have been implicated as cell of origin in basal-like breast cancer, but their anatomical localization remains understudied. Here, we combine collection under the microscope of organoids from reduction mammoplasties and single-cell mRNA sequencing (scRNA-seq) of FACS-sorted luminal epithelial cells with multicolor imaging to profile ducts and terminal duct lobular units (TDLUs) and compare them with breast cancer subtypes. Unsupervised clustering reveals eleven disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…Although much effort has been put into describing the mammary epithelial and stromal cell populations in the human gland by single cell analysis (Nguyen et al, 2018; Chen et al, 2022; Gray et al, 2022), it is not known how these cell types are anatomically distributed within the mammary gland. Previous studies assessing cell localisation in breast tissue sections (Dontu and Ince, 2015; Villadsen et al, 2007) or in micro-collected TDLUs/ducts (Goldhammer et al, 2022; Kohler et al, 2022) also provide limited information of the spatial distribution cell types within TDLUs. As recent advances in technology now enable the imaging of larger tissue volumes, we employed tissue clearing methods, volumetric light sheet microscopy, and mathematical modelling to describe the 3D morphology of TDLUs in the human mammary gland, and investigated whether general branching patterns or principles exist for the human TDLU.…”
Section: Introductionmentioning
confidence: 99%
“…Although much effort has been put into describing the mammary epithelial and stromal cell populations in the human gland by single cell analysis (Nguyen et al, 2018; Chen et al, 2022; Gray et al, 2022), it is not known how these cell types are anatomically distributed within the mammary gland. Previous studies assessing cell localisation in breast tissue sections (Dontu and Ince, 2015; Villadsen et al, 2007) or in micro-collected TDLUs/ducts (Goldhammer et al, 2022; Kohler et al, 2022) also provide limited information of the spatial distribution cell types within TDLUs. As recent advances in technology now enable the imaging of larger tissue volumes, we employed tissue clearing methods, volumetric light sheet microscopy, and mathematical modelling to describe the 3D morphology of TDLUs in the human mammary gland, and investigated whether general branching patterns or principles exist for the human TDLU.…”
Section: Introductionmentioning
confidence: 99%
“…Expression was highly variable among biopsies. However, when present, the typical pattern was a scattered or focal expression in a subset of luminal epithelial cells, mostly aggregating in ductal structures rather than lobular acini, corresponding to the location of several breast progenitor markers 2,22,24 (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…14 This pattern suggests an overlap with a luminal progenitor compartment. 2,22,24 In breast cancer, we detected SSEA-1-positive neoplastic cells in 37% of 220 primary carcinomas. Others have noted similar overall frequencies with antibodies against the LeX epitope.…”
Section: Discussionmentioning
confidence: 96%
“…3f). Further detailed examination revealed many marker genes for other cell types present in breast cancer, including MYLK [42] (Cluster 7, myoepithelial cells), KRT5, KRT14 [43] (Cluster 8, basal cells), KRT15 [44] (Cluster 9, luminal progenitor cells), APOC1 [45] (Cluster 10, macrophages), FCER1A, MRC1 [46] (Clusters 11 and 12, dendritic cells), ADH1B [47], MMP2 [48] (Clusters 13–16, fibroblasts), and IL7R, CD3D [49] (Cluster 17, T cells). Further KEGG enrichment analysis revealed that genes specific to Clusters 1–6 were significantly enriched in many cancer-related pathways (Fig.…”
Section: Resultsmentioning
confidence: 99%